Additively manufactured electrostatic chucks and related methods and structures
Patent Information
- Application Number
- JP2023540034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-31
- Filing Date
- 2021-12-22
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-12-22
AI Technical Summary
が得られる。厚い粗層は、薄い(細)層と比較して品質が低下する可能性があるが(以下を参照)、比較的厚い厚さの層を形成することで、ベースの生産速度が増加する(必要な時間が短縮される)。厚い(粗)層の厚さが増加すると、特定の厚さを有するベースを製造するために形成されなければならない層の総数および必要な層形成工程数が削減される。粗層の厚さは、積層造形法によって形成される層の典型的な範囲内の厚さ、例えば、70、80、90、または100ミクロンから500ミクロンまでの範囲の厚さでよい。粗層の厚さが厚いほど、所定の総厚の完成した多層複合材を形成するのに必要な工程数および時間が削減される。
Smart Images

Figure 0007663696000001 
Figure 0007663696000002 
Figure 0007663696000003
Abstract
Description
[Technical field]
[0001] The present disclosure is in the field of a base component of an electrostatic chuck useful for supporting a workpiece during a process of processing the workpiece, the base component ("base") being fabricated by an additive manufacturing process. [Background technology]
[0002] Electrostatic chucks (or simply "chucks") are used in the processing of semiconductor and microelectronic devices. The chuck holds a workpiece, such as a semiconductor wafer or a microelectronic device substrate, in place to perform processing on the surface of the workpiece. In particular, an electrostatic chuck supports and secures the workpiece on the upper surface of the chuck by generating an attractive electrostatic force between the workpiece and the chuck. A voltage is applied to electrodes contained within the chuck to induce charges of opposite polarity on the workpiece and the chuck.
[0003] Chucks include a variety of structures, devices, and designs that enable the chuck to perform or improve its performance. A typical electrostatic chuck assembly is a multi-component structure that includes a flat upper surface that supports a workpiece, electrical components such as electrodes, conductive coatings, and ground connections to control the electrostatic charge on the chuck and supported workpiece, a temperature control system (e.g., a cooling system) to control the temperature of the chuck and supported workpiece, various other components that may include measurement probes and moveable pins used to support or change the position of the workpiece relative to the chuck, and temperature control medium and electrical connections that extend from the chuck to a tool interface.
[0004] A typical feature of an electrostatic chuck is a base that includes a temperature control system (e.g., a cooling system). The temperature control system includes a pattern of channels or passages formed within the interior of the chuck that allows a fluid (e.g., gas, water, or another liquid) to flow through the interior of the chuck to remove heat from the chuck and control the temperature of a supported workpiece during or after a processing step. For example, a workpiece may undergo an increase in temperature while supported by the chuck during a semiconductor processing step. Cooling fluid passing through the chuck's cooling system can be useful in removing heat from the workpiece and controlling the temperature of the workpiece.
[0005] The base of the electrostatic chuck assembly must be constructed from a high strength dense material that can be processed to form structures with high precision features such as dimensions, flatness, surface roughness, complex temperature control passages, and openings. Current materials used to manufacture the base of the electrostatic chuck include aluminum and other metals or ceramics that can be formed into high precision base structures by machining techniques. Other than alumina, these materials can exhibit high hardness characteristics that make them difficult and expensive to manufacture using high precision machining techniques.
[0006] By existing methods, two opposing pieces are machined in separate pieces (e.g., halves) to form a base that includes an internal (enclosed) cooling passage, and the two separately formed pieces are then joined together, typically by a vacuum brazing or electron beam welding process.
[0007] Vacuum brazing is a specialized process used in the aerospace industry that can be expensive and not readily available. Vacuum brazing involves forming a joint between two opposing surfaces by using a furnace to melt a "filler material" placed between the two surfaces, and then solidifying the molten filler material to form a joint or vacuum brazed joint. The filler material can be a material that melts at a lower temperature than the melting temperature of the two parts being joined. Joints formed by "filler" materials are typically found in vacuum brazed structures. Overall, the formation of two separate parts, each with complex machining steps, combined with the subsequent vacuum brazing step results in high material and processing costs and potentially very long manufacturing lead times.
[0008] An alternative process uses a preformed tube as a placeholder for the cooling channels and then casts material over the tube to form the base.
[0009] Due to the difficulties in manufacturing electrostatic chuck bases, further improvements in electrostatic chuck materials and manufacturing processes are needed. Summary of the Invention
[0010] In one aspect, the present disclosure relates to a chuck (e.g., electrostatic chuck) base comprising an inorganic composite, the base comprising an upper base surface comprised of the inorganic composite, a lower base surface comprised of the inorganic composite, an interior portion between the upper and lower base surfaces comprised of the inorganic composite, and a flow channel (e.g., a cooling channel) surrounded by the inorganic composite within the interior portion, the upper base surface, the lower base surface, and the interior portion including a continuous layer of the inorganic composite extending from the upper base surface to the lower base surface.
[0011] In another aspect, the present disclosure relates to a method of forming a chuck (e.g., electrostatic chuck) base by additive manufacturing, the method including: additively forming a lower portion of the base including a continuous bottom surface, additively forming a middle portion above the lower portion including channels (e.g., cooling channels), and additively forming an upper portion of the base above the middle portion including a continuous top surface. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a side view of the described electrostatic chuck assembly. [Figure 2A] FIG. [Figure 2B] 1 shows a side cutaway view of the base as described. [Figure 2C] 1 shows a side cutaway view of the base as described. [Figure 3A] 4 illustrates steps of the exemplary method described. [Figure 3B] 4 illustrates steps of the exemplary method described. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The drawings are schematic and illustrative and are not necessarily to scale.
[0014] The following description relates to methods for producing dense, substantially non-porous, three-dimensional structures, such as base structures useful as components of electrostatic chuck assemblies, by additive manufacturing processes, including methods commonly referred to as "3D printing" techniques.
[0015] A chuck (e.g., electrostatic chuck) includes a base component that supports various functions of the chuck assembly, including heat dissipation, back gas flow, electrical connections, among others. In advanced applications, the base may also be fabricated to exhibit a thermal expansion coefficient within the range of that of another component of the assembly, the ceramic layer, preferably to enhance the thermal performance and flatness of the chuck assembly. Conventional methods of fabricating the base component of an electrostatic chuck include machining techniques that, depending on the material type of the base, do not easily meet some or all of the physical requirements of the base. For ceramic materials, machining is very difficult and forming embedded (internal) channels (e.g., cooling channels) is very difficult.
[0016] Additive manufacturing processes generally involve a series of individual layer-forming steps that successively form multiple layers of a consolidated feedstock composite derived from layers of a feedstock. Using a series of additive manufacturing steps, each step forming a single layer of the structure, the multiple layers of consolidated feedstock are successively formed into a structure referred to herein as a multi-layer composite (or "composite").
[0017] As used herein, the term "composite" (or "multilayer composite") refers to a structure formed by additive manufacturing by successively forming a series of multiple individual, individually formed layers of solidified feedstock. The composite may take the form of the base of an electrostatic chuck ("base") or may be one or more portions of the base, such as the lower portion and the interior portion of the base. A composite that is a base structure that includes each of a top portion (having a top surface), a bottom portion (having a bottom surface), and an interior portion (e.g., including cooling channels), all three portions formed and held together solely by the layering process of additive manufacturing (e.g., without using a vacuum brazing process or any other type of joining process to join two separately manufactured parts together) may be referred to herein as a "continuous" base or a "continuous layer" of a base.
[0018] The term "continuous" in this context means that the base or layer structure is formed as a single-piece composite structure from multiple successively formed layers. The formation of the composite structure may be a continuous or uninterrupted process. The term "continuous" does not refer to a structure made by forming two separate parts separately and then joining the two separately formed parts together, for example by vacuum brazing techniques or a different type of joining technique. A continuous base structure includes a material that is seamless and / or uniform in composition throughout the base structure. A continuous base does not include seams or boundaries resulting from a joining process, particularly seams or boundaries composed of a joining material or filler material having a different composition than the material of the base. A continuous base structure does not include a base structure formed by joining multiple separate parts, with or without joining or filler materials, even if the separate parts include the same material.
[0019] One specific example of an additive manufacturing technique is a technique commonly referred to as "selective laser melting." Selective laser melting (SLM), also known as direct metal laser melting (DMLM) or laser powder bed fusion (LPBF), is a three-dimensional printing method that uses a high-power density laser to melt solid particles of a feedstock material, allowing the molten (liquid) material of the particles to flow and form successive layers of molten material that can then be cooled and solidified to form a solidified feedstock. According to one particular exemplary method, the particles of the feedstock material can be completely melted to form a liquid (i.e., liquefied), and the liquid material can be flowed to form a substantially continuous, substantially non-porous (e.g., greater than 80, 85, or 90% porosity) film that can then be cooled and hardened as a solidified feedstock layer of a multi-layer composite.
[0020] Selective laser melting includes similar features to another additive manufacturing technique known as selective laser sintering ("SLS"). Selective laser sintering uses laser energy to cause grains of a feedstock material to be sintered, i.e., fused together without melting. This results in structures formed by the heated grains of material having spaces between the grains, making the structure porous. In contrast, using selective laser melting, grains can be completely melted to form dense (substantially non-porous) three-dimensional structures.
[0021] This specification relates to the use of additive manufacturing techniques, such as selective laser melting, to form the base of an electrostatic chuck, which can be a cost-effective technique for forming these base structures, particularly compared to previous methods that involve complex and difficult machining techniques and steps that involve separately forming multiple (e.g., two) individual parts of the base and then joining the multiple parts together to form the completed base structure, such as by a vacuum brazing process.
[0022] Additive manufacturing techniques can be useful for forming base structures made from a wide range of materials, including metallic materials (including alloys) and metal matrix composites. Using additive manufacturing techniques, including selective laser melting techniques, the range of metals, alloys, and metal matrix composites that can potentially be used to form the base can advantageously include materials that are not easily formed into a useful base structure by prior techniques, such as machining techniques. The range of materials available for additive manufacturing techniques includes metals and metal alloys that can be melted by laser energy, such as aluminum alloys, titanium alloys, and various metal matrix composites, some of which are not easily processed by machining. Exemplary materials may exhibit high hardness that may be difficult to process by machining techniques to form precise structures of the base of an electrostatic chuck, including precise dimensions and complex flow paths (e.g., cooling channels). Using additive manufacturing techniques, such materials can be processed to form base structures that include complex enclosed ("embedded," "embedded," or defined) flow paths, even from materials that are similarly difficult to form using standard machining techniques.
[0023] The material used to fabricate the base may be any material useful in fabricating the base of an electrostatic chuck assembly, such as inorganic materials including various metals (including alloys) and metal matrix composites. The term "metal" is used herein consistent with the meaning of the term "metal" in the metallurgical, chemical, and additive manufacturing arts to refer to any metallic or semi-metallic chemical element or an alloy of two or more of these elements.
[0024] The term "metal matrix composite" ("MMC") refers to a composite material fabricated to include at least two components or two phases, one phase being a metal or metal alloy and another phase being a different metal or another non-metallic material, e.g., fibers, particles, or whiskers, dispersed in the metal matrix. The non-metallic material may be carbon-based, inorganic, ceramic, etc. Some exemplary metal matrix composites are comprised of combinations of aluminum alloys with alumina particles, aluminum alloys with carbon, aluminum alloys with silicon, aluminum alloys with silicon carbide (SiC), titanium alloys with TiB2, titanium alloys with silicon, titanium alloys with silicon carbide (SiC).
[0025] Metals and metal alloys that may be useful according to the methods herein include metals and metal alloys that have traditionally been used to fabricate base structures for electrostatic chuck assemblies, as well as other materials that have not been used. Useful or preferred materials include metals such as ferrous alloys (e.g., stainless steel and other types of steel), titanium and titanium alloys, aluminum and aluminum alloys, and various metal matrix composites.
[0026] The present method allows the base to be made from a greater variety of materials than can be used to make the base from prior methods (e.g., machining methods). Because a greater variety of materials is available, the material of the base can be selected to achieve particularly useful or desirable physical properties in view of the materials used for the base of the electrostatic chuck assembly, and for other components of the assembly, such as adjacent ceramic layers.
[0027] The coefficient of thermal expansion ("CTE") is a known physical property of metals, metal matrix composites, and ceramic materials. The materials of the base layers herein may generally have a coefficient of thermal expansion similar to that of various metals and ceramic materials that have previously been used to form components of the base assemblies of electrostatic chucks. Some exemplary materials that may be useful as the base or ceramic layers of the described base assemblies and their approximate CTE values are as follows: Alumina (8.1×10 -6 m / (mK)), aluminum (21~24×10 -6 m / (mK)), aluminum alloy (AlSi7Mg) (21~22×10 -6 m / (mK)), aluminum nitride (5.3×10 -6 m / (mK)), stainless steel 440C (10.2×10 -6 m / (mK)), stainless steel 17-4PH (10.8×10 -6 m / (mK)), Steel M2 (Tool) (11×10 -6 m / (mK)), titanium (8.6×10 -6 m / (mK)), titanium alloy Ti-6Al-4v (TC4) (8.7-9.1×10 -6 m / (mK)).
[0028] Illustratively, the metal or metal matrix composite material used to make the described base has a useful or preferred thermal expansion coefficient of 4×10 -6 m / (m K)~30×10 -6 m / (m K), e.g. 5×10 -6 m / (mK)~25×10 -6 It may be within the range of m / (m K).
[0029] In certain preferred base structures and electrostatic chuck assemblies, the material of the base may preferably have a coefficient of thermal expansion that matches or is similar to the coefficient of thermal expansion of adjacent layers of the assembly. Often, as part of an electrostatic chuck assembly, the base layer is positioned near, adjacent, or otherwise sufficiently close to the ceramic layer of the assembly such that the base layer and the ceramic layer are subjected to similar temperature conditions and the thermal expansion of one is influenced (e.g., limited) by the other. In such cases, a useful combination of the base layer and the ceramic layer of the assembly may be composed of materials having approximately equal coefficients of thermal expansion. A preferred base of an electrostatic chuck assembly may have a coefficient of thermal expansion similar to that of the ceramic layer that is part of the same chuck assembly. The coefficient of thermal expansion of the base may be within 25, 20, 15, 10, or 5% of the coefficient of thermal expansion (m / (m-degrees Kelvin)) of the ceramic layer.
[0030] The layer-by-layer approach of the described additive manufacturing techniques allows the formation of intricate, highly precise, complex shapes that are highly effective structures when included in an electrostatic chuck base. Compared to machining techniques, the described additive manufacturing techniques can be more efficient in producing patterns (e.g., channels) that are highly complex, cover a large portion of the surface area of the base, occupy a large volume of the base structure relative to the total volume of the base structure, and have various cross-sectional shapes or specially designed (specialized) patterns. These patterns can be voids, openings, depressions, cavities, grooves, notches, shapes designed for various functions. These functions include heating, cooling, weight reduction, enhancing mechanical properties, providing a support surface for stability, and other possible functions. In one example, the patterns are channels for cooling, through which a coolant can flow to remove heat from the chuck and the workpiece supported thereon.
[0031] The channels formed by additive manufacturing techniques may be of different or varied shapes (cross-section), patterns (relative to the surface of the base assembly), and sizes (e.g., width or diameter of the channel), arrangements (relative location of the channel), and surface features that allow for smooth and efficient flow of fluid through the channels. For example, machining processes typically produce square channels, but additive manufacturing techniques can be useful for producing circular channels, which can result in improved flow (laminar flow) through the channels compared to turbulent flow through channels having square cross-sections. As another example, the channels may be formed to exhibit asymmetric cross-sections, which allows for the design of channels with improved heat transfer efficiency through the surface of the base. In another example, additive manufacturing techniques can form two or more channels with interconnections between them. The two or more channels include various cross-sectional shapes. In a further example, the two or more channels may have different cross-sectional shapes from each other.
[0032] Yet another optional feature of the flow channels formed as described may be a pattern of flow channels with respect to the surface area (usually circular) of the base and base assembly, designed to improve the efficiency of heat transfer for the particular workpiece and non-uniform features of the particular workpiece that the base assembly may support. This feature, sometimes referred to as "conformal cooling," allows for a pattern of flow channels in the base to be designed and formed in the base with a dedicated design to match the particular heat removal requirements of the workpiece (e.g., semiconductor or microelectronic device or wafer) that is supported by the electrostatic chuck assembly during use. Additionally, additive manufacturing techniques allow for less complex manufacturing methods for forming the base, including fewer total manufacturing steps, compared to prior methods that form two separate base parts and join the two parts using a vacuum brazing process. Additive manufacturing allows for a fully (or substantially fully) functional base layer of the electrostatic chuck to be made using a single manufacturing process (a single additive manufacturing "step"), resulting in high manufacturing efficiency (high manufacturing throughput) with a reduced amount of time per unit. A complete base layer with substantially all the required structures (including bottom, inner, and top portions) can be produced by a single series of additive manufacturing steps. For example, what can be referred to as a "one-step" additive manufacturing process for forming the base structure can form many, most, or all of the required structures of the base (including bottom, inner, and top portions) as a single continuous layer as the described multi-layer composite. A one-step additive manufacturing process avoids the need to individually form multiple separate parts by separate steps, followed by an additional step of joining the multiple separately formed parts together to form a functional base structure.
[0033] Additionally, additive manufacturing techniques can be used to form bases with highly accurate dimensions, e.g., dimensional accuracy of the base within + / - 0.13 mm, location (or position) accuracy of the base within + / - 0.13 mm, perpendicularity within + / - 0.01 mm, flatness within + / - 0.04 mm, parallelism less than 0.05 mm, angular accuracy within + / - 0.5°, and / or leakage rates of enclosed features (e.g., flow channels) of 10 -10 Less than mbarL / s.
[0034] According to an exemplary method, the base can be fabricated to exhibit a high level of flatness, e.g., an "ultra-flat" surface, where the flatness is measured on the top surface of the metal matrix composite layer of the assembly, such that the high level of flatness of the base can improve the flatness of the electrostatic chuck assembly. Flatness is a typical characteristic of an electrostatic chuck, or the base component of the chuck, and can be measured by known techniques, such as by using a coordinate measuring machine. Generally, flatness is measured and reported as the difference in height (in the z-direction) between the peaks (highest measured points) and valleys (lowest measured points) of the measured surface, and is given in units of distance, e.g., microns. A 300 millimeter diameter base fabricated solely by machining processes can be fabricated to exhibit a flatness as low as 30 microns. For a comparable base (300 millimeter diameter) surface described herein, forming the base by an additive manufacturing process and then further processing the base surface by a machining process can improve the flatness of the base relative to a base fabricated solely by machining. The flatness of the base surface after additive manufacturing can be less than 45 or 50 microns, e.g., as low as 40 microns. The surface may be further treated by a machining step such as lapping or polishing to achieve an even lesser flatness, for example less than 30 microns, such as less than 20 microns, or even as low as about 15 microns.
[0035] In certain advanced applications of electrostatic chuck assemblies (e.g., Cryo, low angle implants), a useful chuck assembly should exhibit ultra-high flatness as measured at the top surface of the assembly (e.g., the top of the ceramic layer). A preferred flatness value for a particular application of the chuck assembly may be less than 10 microns as measured at the top ceramic surface for a 300 millimeter chuck. It is also important to maintain this ultra-high flatness property over a wide range of operating temperatures. The flatness level of the chuck assembly over a range of temperatures can be improved by closely matching the thermal expansion coefficient values of the different layers (ceramic and base layers) of the chuck assembly, by improved heat dissipation from the assembly to extract heat (heat removal by fluid flow through the base), and also by improved flatness of the surfaces of these layers at the junctions between the layers. Materials used to form the base of the chuck assembly, such as titanium, titanium alloys, and metal matrix composites, can provide improved CTE matching and improved flatness compared to previous materials commonly used to form chuck bases, such as aluminum, which are less stiff than these materials.
[0036] Furthermore, the exemplary method of the present disclosure can be used to produce a base that exhibits relatively low roughness. Roughness is a typical characteristic of an electrostatic chuck base, and roughness can be measured by known analytical techniques, including by using, for example, a 3D laser microscope or a stylus profilometer, as represented by the arithmetic mean of the surface roughness curve (denoted as "Ra"). Ra is calculated as the roughness average of the measured microscopic peaks and valleys of the surface. Exemplary surfaces of bases produced by the described additive manufacturing methods and having reduced additive manufacturing surface roughness by subsequent machining steps can have a low surface roughness (Ra) of less than 1 micron, for example less than 0.5 microns, or as low as about 0.1 microns. Roughness (Ra) can be measured by one of a variety of standard methods, such as ISO4287-1:1984 or ASTM F 1048. The improved accuracy of forming the base allows for greater improvements in the accuracy of forming a chuck assembly that includes a ceramic layer attached to the base, including improved flatness measured at the top of the ceramic layer. A typical base produced by machining methods having a diameter of 300 millimeters can be combined with a ceramic layer to form an assembly exhibiting a flatness as low as 30 microns measured at the upper ceramic surface. In an exemplary embodiment, the base layer herein can be combined with a comparable ceramic layer to form an assembly having a diameter of 300 millimeters exhibiting a flatness as low as less than 30 microns, such as less than 25 microns, such as less than 20 microns, or as low as about 15 or 10 microns measured at the upper ceramic surface. To achieve this low level of flatness of the metal matrix composite layer of the base assembly, the base layer can be formed by additive manufacturing, and the surface of the base assembly (contacting the metal matrix composite layer) can be machined to improve the flatness of the surface produced by the additive manufacturing process.
[0037] Additional processes can be utilized after the additive manufacturing process. For example, a powder removal process can be performed to remove loose powder generated during the additive manufacturing process as a by-product. The powder removal process removes loose powder from the surfaces of the chuck or the channel by an ultrasonic vibration assisted vacuum system, followed by blowing compressed air through the channel inlet to carry the loose powder away. In another example, the additional process can include a cleaning process to remove contamination on the chuck, such as oil or grease, caused during the additive manufacturing process. In a further example, a thermal process can be used to reduce thermal stresses induced during the additive manufacturing process.
[0038] The methods herein use additive manufacturing techniques to form a base structure (e.g., a continuous base layer, or a portion of a base layer) by successively forming multiple layers of a composite. The composite is formed from multiple layers, each of which individually can have any useful thickness, and from one or more materials that can melt and flow to form a dense inorganic (e.g., metal or metal matrix composite) solid that is useful as the substantially non-porous material of the base structure.
[0039] In general, the base may be considered to have the form of a flat, thin, typically circular structure (as viewed from the top and bottom), such as a flat disk including two opposing flat, circular surfaces of a certain thickness. The two opposing surfaces serve as the top and bottom of the base layer. An interior portion of the base resides between the two opposing surfaces. The interior portion may include a system of enclosed channels (e.g., cooling channels) that extend through the interior portion in a meandering, turning, twisting, circuitous, or serpentine path.
[0040] The channels can accommodate a flow of fluid (e.g., water or another liquid or gaseous fluid) that can be used to control the temperature of the base during operation of the base. Other structures may also be formed in the surface of the base, such as vertical mouths ("openings") that extend between the thickness and between two opposing surfaces of the base (from top to bottom and throughout the thickness), or channels or grooves in one or both of the top and bottom surfaces.
[0041] The functional base layer of the chuck assembly can be considered to include at least three distinct parts: a lower part including a bottom surface, an upper part including a top surface opposite the bottom surface, and a middle ("internal") part disposed between the upper and lower parts and which can include flow channels (e.g., cooling channels). Preferably, according to the described preferred method, all three parts and all layers thereof can be manufactured by additive manufacturing, whereby a single (preferably continuous) series of layer formation steps is used, optionally and preferably all layer formation steps are performed in a single additive manufacturing apparatus to form all layers of the functional base layer as continuous seamless layers of inorganic material without any seams or internal boundaries, such as those that may be formed by a joining process (e.g., vacuum brazing). By "consecutive" it is meant that each layer formation step in a series of additive manufacturing steps is performed sequentially without any different type of step (e.g., any type of non-layer formation step) between any two layer formation steps, and without a joining step (different from the additive manufacturing step) in which two parts of the base layer are joined to each other using a filler material, a brazing material, an adhesive, etc.
[0042] A method, such as one example of a method described herein, can include forming, by additive manufacturing, a lower portion of a base including a bottom surface, forming, by additive manufacturing, an intermediate portion of the base above the lower portion including a cooling channel, and forming, by additive manufacturing, an upper portion of the base above the intermediate portion including a top surface.
[0043] Each layer of the composite can be formed as desired from a desired material at a desired thickness to produce a base layer in the form of a multi-layer composite having desired properties. With an exemplary additive manufacturing process, each layer is made from a collection of particles (called a "feedstock"), typically in the form of a powder. The feedstock contains small particles made up of one or a variety of different inorganic materials that can be melted by a high-energy laser to liquefy and flow to form successive layers of molten material, and then cooled and solidified to form the layers of the multi-layer composite.
[0044] Particles useful according to the present invention may be any particles that can be processed to form the useful multi-layer composites described. The particles may be included in a feedstock in the form of a powder that includes, consists of, or consists essentially of inorganic particles that can be fused using energy from a high energy laser to form layers of the multi-layer composite.
[0045] Examples of useful particles include inorganic particles that can be melted or liquefied by laser energy as described to form layers of the base structure. Examples of such particles include inorganic particles made of metals (including alloys) and metal matrix composites. Some useful examples generally include metals and metal alloys, such as aluminum, titanium, and their alloys, as well as metal matrix composites. One specific example of a useful aluminum alloy is AlSiMg. One specific example of a useful titanium alloy is Ti6Al4V.
[0046] Useful particles of the feedstock can be of any effective size (e.g., average particle size) or range of sizes, including small or relatively small particles on the micron scale (e.g., average sizes less than 500 microns, less than 100 microns, less than 50 microns, less than 10 microns, or less than 5 microns).
[0047] The particles can be selected to achieve the effectiveness of the described processes, can be included in the feedstock, can be formed into a feedstock layer, can be melted and flowed to form successive layers, and can be cooled and solidified to form the feedstock into a layer of a multi-layer composite. The size, shape, and chemical makeup of the particles can be any that are effective for these purposes.
[0048] The particles may be in the form of a feedstock composite that can be used in the additive manufacturing process herein. By way of example, a feedstock useful in an additive manufacturing process may include particles that can be melted to form a continuous, substantially non-porous layer of a multi-layer composite. The feedstock material need not include other materials, but may optionally include small amounts of other materials, if desired. Exemplary feedstock composites may contain at least 80, 90, or 95, 98, or 99% inorganic particles by weight, based on the total weight of the feedstock composite. If desired, one or more other components, such as flow aids, surfactants, lubricants, leveling agents, etc., may be present in small amounts.
[0049] Each layer of the multi-layer composite may be formed to have any useful thickness. The thickness of a layer of the multi-layer composite is measured for the layer of composite after the layer is formed by melting particles of the feedstock layers to form successively melted and then solidified layers of composite. Exemplary thicknesses of the layers of composite may range from 30 microns to 100 microns, 200 microns, or more, such as 30 to 50, 60, 70, 80 microns to 90, 100, 150, 200, 300, 400, or 500 microns. In an exemplary composite structure, all layers of the composite may have the same thickness or substantially the same thickness. In other exemplary composite structures, different layers of the composite may have different thicknesses, rather than all layers having the same thickness.
[0050] According to certain exemplary methods and base structures herein, the base may be fabricated by an additive manufacturing process by forming layers of composite material to have different thicknesses in different portions of the base. Examples of these methods and structures include forming one or more layers (called "thin layers") having a thinner thickness, for example in the top and bottom portions of the base, and forming layers ("coarse layers") having a thicker thickness, for example in the interior (or middle) portion of the base between the top and bottom portions. Alternatively, the middle portion may include a fine layer, and the upper and bottom portions may include a coarse layer.
[0051] The location of one or more fine layers as part of a multi-layer composite (e.g., in the form of a base layer) may be in any useful location relative to the coarse layer. Various locations of the coarse and fine layers in the composite, as well as various sequences of formation of the coarse layers relative to the fine layers, may be effective. However, according to certain embodiments of the described base structure and related methods, one or more fine layers may preferably be present on one or more surfaces of the base, and coarse layers may be present on the interior portion of the same base. That is, fine and coarse layers may be formed in alternation. Since fine layers may exhibit more desirable physical properties compared to coarse layers (see below), it may be desirable for fine layers to be located on one or more surfaces. Layers in the interior portion of the base, where high quality is less important, may be made with coarse layers to increase manufacturing efficiency (see below).
[0052] Forming layers of the base with different thicknesses can produce advantages in terms of processing efficiency and also in terms of the physical properties of the base (or parts of the base). Forming one or more "rough" layers of a thicker thickness has the beneficial effect of increasing the production speed and efficiency of the base. Although thicker rough layers may be of reduced quality compared to thinner (fine) layers (see below), forming layers of a relatively thicker thickness increases the production speed of the base (reducing the time required). Increasing the thickness of the thicker (rough) layers reduces the total number of layers that must be formed and the number of layer formation steps required to produce a base with a particular thickness. The thickness of the rough layers can be within the typical range of thicknesses for layers formed by additive manufacturing processes, for example, from 70, 80, 90, or 100 microns to 500 microns. The thicker the rough layers are, the fewer the number of steps and time required to form a finished multilayer composite of a given total thickness.
[0053] The thickness of a layer formed by an additive manufacturing technique can affect the physical properties (quality) of the layer when the layer formation process uses the same feedstock and the same laser. For example, a thinner layer may be formed to contain fewer internal open spaces, or "pores," compared to a thicker layer formed using the same feedstock and the same laser. The presence of pores in a layer can be measured and expressed by the apparent density of the layer. In general, when using an additive manufacturing process that applies the same laser and the same laser power to the feedstock layer for the same amount of time, the apparent density of a thicker (coarse) layer will be lower than the apparent density of a similar (e.g., fine) layer of a thinner thickness but made from the same feedstock.
[0054] Apparent density refers to the measured density of a composite layer relative to the actual (or theoretical) density of the material used to form the layer in 100% dense, non-porous (zero porosity) form. Composite layers are usually continuous dense materials because they are formed by a process that allows melting particles of a feedstock, flowing the molten particles, and forming a continuous layer (e.g., a "film") from the liquefied particle material. However, the continuous dense material formed is generally not 100% dense and contains a small amount of voids or pores that are not removed during the layer formation process. Pores can cause a decrease in the performance of the base, especially when the base is used in a process under reduced pressure, by allowing fluids (e.g., cooling water) to leak from the flow passages through the porous material of the base to the outside of the base.
[0055] In many cases, pores in a layer or composite are optically visible, with or without magnification, at the surface or in the interior of the composite. Alternatively, these voids can be detected as a decrease in density (apparent density) of a layer of the composite or a portion of the composite. A layer formed with no voids (100% dense inorganic material with 0% pores) has a density equal to the density of the non-porous inorganic material used to make the layer. A mass of inorganic material containing pores has a density (apparent density) slightly lower than the density of the inorganic material.
[0056] The density of a layer (or apparent density, if the layer contains a quantity of pores) is a measure of the mass of the layer divided by the volume of the layer (including pore volume), divided by the actual (theoretical) density value of the material used to form the layer with zero pore volume, and reported as a percentage of the actual density. The apparent density value of a described layer or part of a composite (or base layer) is usually relatively high, and may, for example, exceed 80, 90, 92, 96, 98, or 99% of the actual density of the material used to form the layer.
[0057] When forming a layer of a composite material from inorganic particles, energy from a high power laser is used to melt the inorganic particles formed as a feedstock layer. The molten particles flow to form a continuous layer (e.g., a "film") that solidifies as a layer of the composite material. Ideally (in theory), the laser energy completely melts all particles of the feedstock composite material used to make the layer, and the flow of liquefied particulate material forms a void-free liquid layer that solidifies to form a void-free solid. In practice, however, layers formed in this manner may generally contain defects, voids, or partially unmelted particles, and the amount of these defects will be greater in layers formed to have greater thicknesses (for the same feedstock material, the same laser, and for equal exposure times to an area of the feedstock layer).
[0058] The process of forming a coarse layer of a composite includes forming a feedstock layer having a higher thickness and fusing the grains of the feedstock. Using an equal amount of laser power for the coarse layer (having more grains) as can be used to fuse the grains of a fine layer (having fewer grains) and an equal time to expose the laser to the area of the feedstock, the amount of laser power available per grain to fuse the number of grains of the thicker feedstock layer (having more grains) is less. Due to the lower laser energy received per grain of the feedstock layer (higher grain count due to the coarse feedstock layer), the coarse layer may have a higher level of defects compared to the fine layer.
[0059] The greater the amount of defects, the lower the apparent density may be. The apparent density of the coarse layer will usually be lower than the apparent density of the fine layer when using the same feedstock, the same laser, and the same time of application of the laser to the area of the feedstock layer. In the exemplary method and base structure, the apparent density of any layer of the base may preferably be at least 98 or 99%. More specifically, the apparent density of the coarse layer of the base may preferably be at least 99.0%, such as at least 99.2 or 99.4%. The apparent density of the fine layer of the base may preferably be greater than the apparent density of the coarse layer of the same base, and may be at least 99.4%, such as at least 99.6%.
[0060] Forming one or more "fine" layers of low layer thickness can be useful to improve the physical qualities of the base structure. Finer layers of composites produced by additive manufacturing have been found to exhibit useful or favorable physical properties, such as high density and a relatively low amount of defects, such as pores, formed within the layer.
[0061] On the other hand, forming multiple thin layers having smaller thicknesses during an additive manufacturing process slows down the production rate of the multi-layer composite, i.e., increases the number of steps and time required, because more thin (thinner) layers must be formed to produce a multi-layer composite having a particular thickness, and more additive manufacturing steps are required to create a multi-layer composite of a given thickness.
[0062] The thickness of the thin layer may be within the typical range of thicknesses of layers formed by additive manufacturing processes, particularly at the lower end such as a thickness in the range of 30 microns to 100 microns, for example 30 to 50, 60, 70, 80, or 90 microns.
[0063] The described electrostatic chuck is a multi-piece (or "multi-component) structure that includes multiple components assembled together in layers to form an electrostatic chuck assembly. The assembly includes various structures and features, which are unique to the electrostatic chuck assembly, in which electrostatic attraction holds the workpiece in place at the top surface of the chuck (the "workpiece contact surface"), allowing the chuck to support the workpiece (e.g., semiconductor substrate, microelectronic device, semiconductor wafer, precursor thereof) during processing. Examples of workpieces used with electrostatic chucks include semiconductor wafers, flat screen displays, solar cells, reticles, photomasks, and the like. The workpiece can have an area of a circular 100 millimeter diameter wafer, a 200 millimeter diameter wafer, a 300 millimeter diameter wafer, or a 450 millimeter diameter wafer or greater.
[0064] The chuck includes an upper "workpiece contact surface" configured to support a workpiece during processing. The upper surface typically has a circular surface area with a circular edge that defines the perimeter of both the workpiece contact surface and the multi-layer chuck. As used herein, the term "workpiece contact surface" refers to the upper exposed surface of the electrostatic chuck that contacts the workpiece during use and includes a "primary field" having an upper surface that is constructed of a ceramic material and typically includes a protrusion on the upper surface and an optional conductive coating that may cover at least a portion of the upper surface. The workpiece is held at the workpiece contact surface on the upper surface of the ceramic material, in contact with the upper surface of the protrusion, and is held or "clamped" against the electrostatic chuck during use of the electrostatic chuck. Exemplary electrostatic chuck assemblies can be used in AC and DC Coulomb type chucks and Johnsen-Rahbek type chucks. In this embodiment, the upper "workpiece contact surface" is formed by depositing thin layers of a composite material using an additive manufacturing process.
[0065] The chuck assembly (or "chuck" for short) also includes several other layers, devices, structures, and features that are necessary or optional for the chuck to function. These include an electrode layer that creates an electrostatic attraction between the chuck and the workpiece to hold the workpiece in place during processing, a grounding device such as a ground layer and associated electrical connections, measurement devices for measuring pressure, temperature, or electrical properties during the processing steps, gas flow conduits as part of the temperature control function, a rear gas flow function for gas flow and pressure control between the workpiece contact surface and the workpiece, conductive surface coatings, etc.
[0066] One layer of a typical chuck assembly is a ceramic layer (aka dielectric layer) on the upper portion of the assembly. The ceramic layer may be the top layer of the assembly, or may include the top surface of the chuck other than a conductive coating, protrusions, etc. disposed on the top surface of the ceramic layer. The conductive coating on the top surface may be connected to electrical ground via a ground layer, ground pin, etc. also included in the chuck assembly. The ceramic layer may be comprised of any useful ceramic material, such as alumina, aluminum nitride, quartz, SiO2 (glass), among others. The ceramic layer may be comprised of a single (unitary) layer of material, or may be comprised of two or more different materials, e.g., multiple layers of different materials, as desired. The total thickness of the ceramic layer (having one or more layers of ceramic material) may be any effective thickness, e.g., a thickness in the range of 1 to 10 millimeters, e.g., 1 to 5 millimeters.
[0067] The ceramic layer is supported underneath by a base layer (abbreviated "base") as described herein which may be composed of a metal such as aluminum, an aluminum alloy, titanium, a titanium alloy, stainless steel, a metal matrix composite, among others as described.
[0068] Typically between the ceramic layer and the base there is one or more of a bonding layer (e.g., a polymer adhesive), an electrode, a ground layer, an insulating layer that enables the electrodes and other layers to function electrically, or additional circuitry.
[0069] An example of a useful chuck assembly is shown in FIG. 1. The chuck assembly 10 includes a base 12, a ceramic layer (assembly) 14, and a bonding layer 16 that bonds the base 12 to the ceramic layer 14. The ceramic layer 14 includes subcomponents such as electrodes. The upper surface of the ceramic layer 14 has a pattern of protrusions 18. As shown, a wafer 20 is supported by the protrusions. A cavity 22 exists between the lower surface of the wafer 20 and the top of the ceramic layer 14. The cavity 22 is formed by the protrusions 18 located on the upper surface of the ceramic layer 14, which support the wafer 20 a short distance above the upper surface of the ceramic layer 18. During use, a flow of gas (e.g., cooling gas) can pass through the cavity 22 between the wafer 20 and the ceramic layer 14 to control (e.g., reduce) the temperature of the wafer 20. The base 12 includes cooling channels (e.g., cooling channels) not specifically shown.
[0070] The chuck assembly herein includes a base component that includes channels (e.g., cooling channels). According to the method described herein, the entire structure of the base and the internal channels is fabricated using additive manufacturing techniques, such as selective laser melting techniques. The system of channels can be formed in the base during additive manufacturing of the base as a pattern of open spaces (e.g., "void" spaces) that form connected channels distributed in the multi-layer composite formed in the base structure. That is, the channels are defined by the absence of multi-layer composite material at the location of the channels, and no other structure is required to form or define the structure of the channels. The channels run throughout the interior of the base layer and do not require any structure or surface other than the channel voids formed in the base layer during the formation of the base by additive manufacturing. The channels can be interconnected with each other. The channels are defined by the surfaces of the multi-layer composite without other materials. In particular, the channels do not include additional structures other than the structure of the multi-layer composite, such as separate tubes, pipes, or conduits formed separately from the composite and disposed in the composite base layer. In use, a fluid, which may be a gas or a liquid, flows through the channel in contact with side walls of the channel constructed from the multi-layer composite, with no other material forming or defining the inner surface of the channel.
[0071] The channels (e.g., cooling channels) function to circulate a fluid (e.g., water or another liquid for heat exchange) through an interior portion of the base to control the temperature of the base. The channels are formed within the base and extend horizontally relative to the area of the base when viewed vertically (e.g., from above, from a "top" surface). Alternatively, the channels may extend in a direction other than horizontal, such as vertically. The channels include at least one inlet in the base that allows the fluid to enter the base and at least one outlet that allows the fluid to exit the base.
[0072] The channels (e.g., cooling channels) or portions thereof that are part of the base may be in any useful pattern relative to the area of the base at any useful location within the base. Advantageously, the channels of the described base may be formed in the base to achieve improved performance (heat exchange, e.g., cooling) relative to channels formed by machining techniques. Channels formed by additive manufacturing techniques may be more precise, may be formed with alternative cross-sectional shapes (that cannot be formed by machining), may be formed in more complex (serpentine) patterns, and may be formed with a higher density of channels in the base relative to channels formed by machining (channels that occupy a greater percentage of the total volume of the base structure compared to channels formed by machining). Examples of channel cross-sectional shapes include circular, triangular, hexagonal, dome-shaped (curved at one end, flat at the other end), and teardrop-shaped shapes. The cross-sectional shapes of the channels are achieved by the additive manufacturing process described above.
[0073] 2A and 2B show a single example of a base 100 of the present specification. The base 100 includes a perimeter 110, an upper surface 102, a lower surface 104, and a thickness between the two opposing surfaces. Cooling channels 106 (shown as having a circular cross section) are present in a serpentine pattern in the interior portion of the base.
[0074] FIG. 2C shows examples of various cooling channel cross-sectional shapes, including cross-sections that are triangular (i), hexagonal (ii), dome-shaped (curved at one end and flat at the opposite end) (iii), and teardrop-shaped (iv).
[0075] These or other cross-sectional shapes may also incorporate other features of the flow channels (e.g., cooling channels) into the base design that are not possible or easily achievable using machining techniques. For example, the flow channels may be formed to have a larger volume toward the top surface of the base compared to the bottom surface of the base. The flow channels may be shaped such that the majority of the flow channels are toward the top surface, or the flow channels are located closer to the top surface and further from the bottom surface. Alternatively or additionally, the heat exchange loops may be located at various levels of the thickness of the base, rather than at a single level of the thickness of the base. Some portions of the heat exchange loops may be located at different thickness levels (closer to or further from the top surface) compared to other portions. Alternatively or additionally, the cross-section of the flow channels may vary based on location within the base. The cross-section may be smaller in size (cross-sectional area) or differently shaped in portions of the base closer to the center of the base and larger or differently shaped at the edges (or vice versa) to allow for more uniform heat transfer.
[0076] The described bases can be made by additive manufacturing techniques that use a series of individual layer-by-layer processes to form dense metal or metal matrix composite multi-layer composite structures. As an example, a technique called selective laser melting (SLM) is one type of additive manufacturing technique that can be used to form multi-layer composites layer by layer. Selective laser melting uses high power laser energy to selectively melt and flow metal or metal matrix composite particles in a feedstock metal matrix composite layer to form a substantially continuous solidified feedstock layer.
[0077] More specifically, multi-layer composites can be made by successive steps that produce multiple thin cross-sections ("solidified feedstock" herein "layers") of a larger three-dimensional structure (the composite). A layer of feedstock is formed, the layer including many particles of a metal or metal matrix composite. Laser energy is selectively applied to the feedstock layer over a portion of the layer of feedstock. The laser energy melts particles in the portion of the feedstock exposed to the laser energy. The melted particles liquefy and flow into successive layers of molten particle material, which then cool and solidify as a layer of solidified feedstock. After the initial layer of solidified feedstock is formed, an additional thin layer of feedstock is deposited on top of the completed layer including the solidified feedstock. This process is repeated to form multiple layers of solidified feedstock, each layer formed on top of and attached to the top surface of the previous layer. Multiple layers are deposited, one on top of each completed layer, to form a multi-layer composite that is a composite of each layer of solidified feedstock. The multiple layers may be of the same composition and thickness, or may be of different compositions and different layer thicknesses.
[0078] An example of a selective laser melt deposition modeling technique (200) useful for making the described multi-layer composites is shown in FIG. 3A. The process can be carried out using a commercially available selective laser melt deposition modeling device and particles forming the feedstock. The feedstock 202 is a powder containing a collection of inorganic particles. According to the exemplary steps shown in FIG. 3A, the powder feedstock (202) contained in the selective laser melt deposition modeling device is formed as a uniform layer on the build plate of the device (204, 206). In the next step (208), an electromagnetic radiation source (e.g., a high-power laser) selectively irradiates a portion of this first layer of the feedstock with radiation of a wavelength and energy that melts the particles. The molten particles flow into a continuous film and then solidify by cooling. The layer of the feedstock may be a fine layer or a coarse layer and may have any useful thickness. The solidified material of the molten particles forms the solidified feedstock in the irradiated portion. The portion of the feedstock layer that is not formed into a solidified feedstock remains as the original liquid feedstock.
[0079] The build plate moves down (210) and a second layer of powder feedstock (either a fine layer or a coarse layer) is formed as a second uniform layer (212) over the first feedstock layer and over the solidified feedstock of the first feedstock layer. An electromagnetic radiation source then selectively irradiates (214) a portion of the second layer, melting the particles in that portion. The melted portion then cools to form a solidified feedstock in a portion of the second layer. The portion of the second layer that is not formed into a solidified feedstock remains as the original powder feedstock. Steps 212, 214, and 216 are repeated (218) to form a completed multi-layered solidified feedstock composite surrounded by the original liquid feedstock (202).
[0080] The multi-layer solidified feedstock composite is a body containing the solidified feedstock of each formed layer, composed of multiple successive layers made from the material of the molten particles of the feedstock. The original feedstock (202) can be removed and separated (218) from the multi-layer composite.
[0081] Referring to FIG. 3B, a commercially available selective laser melting deposition modeling apparatus (230) may be used to carry out an exemplary process using a powder feedstock (232) according to the present disclosure. According to an exemplary step of the method, the feedstock (232) is formed as a uniform feedstock layer (234) on a build plate (238) of the apparatus (230). A laser (236) irradiates a portion of the first layer (234) with electromagnetic radiation (233), which causes the feedstock particles to melt and flow into successive layers that can then be cooled to form a first solidified feedstock (240) in the portion. The portion (234) of the feedstock layer that is not formed into a solidified feedstock (240) remains as the original feedstock (232). The build plate (238) moves downward (214) and a second or next feedstock layer (242) is formed on the first layer (234) and the first solidified feedstock (240). The laser (236) then selectively irradiates portions of the second layer (242) with electromagnetic radiation (233) to melt and flow the particles of the feedstock to form successive layers that can be cooled to form a solidified feedstock from the second layer. Portions of the second layer that are not formed into a solidified feedstock remain as the original powder feedstock. This sequence is repeated (250) to form a completed multi-layered solidified feedstock composite (252) surrounded by the original feedstock (232). The multi-layered solidified feedstock composite (252) is a body that includes the solidified feedstock of each formed layer and is composed of material from the molten particles of the feedstock. The original feedstock (232) can be removed and separated from the multi-layered composite (252).
Claims
1. an upper chuck base surface made of an inorganic composite material; a lower chuck base surface made of the inorganic composite material; an interior portion between the upper chuck base surface and the lower chuck base surface, the interior portion being made of the inorganic composite material; a flow path formed by the inorganic composite material within the inner portion; the upper chuck base surface, the lower chuck base surface, and the interior portion including a continuous layer of the inorganic composite extending from the upper chuck base surface to the lower chuck base surface; The chuck base, wherein at least one of the upper chuck base surface, the lower chuck base surface, or the interior portion has a density of at least 99.0%.
2. The chuck base of claim 1 , wherein the continuous layer of the inorganic composite is seamless and the inorganic composite is uniform in composition.
3. The chuck base of claim 1, wherein at least one of the upper chuck base surface, the lower chuck base surface, or the inner portion has a density of at least 99.6%.
4. The chuck base of claim 1 , wherein the channels are interconnected.
5. 1. A method of forming a chuck base by additive manufacturing, comprising: forming a lower portion of the chuck base including a continuous bottom surface by additive manufacturing; forming an intermediate portion of the chuck base including a cooling channel on the lower portion of the chuck base by additive manufacturing; forming an upper portion of the chuck base including a continuous upper surface on the intermediate portion of the chuck base by additive manufacturing; Including, forming the lower portion of the chuck base by additive manufacturing includes forming a plurality of first sub-layers, each first sub-layer having a first sub-layer thickness; additively forming the intermediate portion of the chuck base includes forming a plurality of coarse layers, each coarse layer having a coarse layer thickness greater than the fine layer thickness; The method, wherein forming the upper portion of the chuck base by additive manufacturing includes forming a plurality of second sub-layers, each second sub-layer having a second sub-layer thickness.
6. The method of claim 5, wherein the inorganic material of the intermediate portion of the chuck base has an apparent density of less than 99.0%.
7. The method of claim 5, wherein the inorganic material of the intermediate portion of the chuck base has an apparent density of less than 99.6%.
Citation Information
Patent Citations
Method for producing ceramic molding
JP2019081357A
Material powder for additional molding, structure, semiconductor manufacturing device component, and semiconductor manufacturing device
JP2019084823A
Mounting table and substrate processing apparatus
JP2020126900A